Investigation of dynamic glass transitions and structure transformations in cryovacuum condensates of ethanol - Aldiyarov, A.; Aryutkina, M.; Drobyshev, A.; Kaikanov, M.; Kurnosov, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
IR spectrometric investigation of dynamic glass transition from the rotationally disordered crystal into orientationally disordered crystal of ethanol was carried out. The examples considered are thin films formed from the gas phase at a substrate temperature of T = 16 K. The measurements were performed using the experimental apparatus which has been described in detail in our recent work. The thickness of the sample was d = 2 μm, the typical rate of annealing was approximately 10 K/min. The obtained results are compared with the phase diagram of solid ethanol proposed by M.A. Ramos et al. We observe a good agreement between the temperature intervals of existence of amorphous and crystalline states. The low-temperature amorphous phase (12–70 K) is described by the present authors as amorphous solid ethanol by analogy with the amorphous solid water.